EVALUASI STATUS KESUBURAN KIMIA TANAH PADA KAWASAN PERBUKITAN MENOREH DI DESA BIGARAN KECAMATAN BOROBUDUR KABUPATEN MAGELANG JAWA TENGAH - Listianto, Fernanda Ghifary; Peniwiratri, Lelanti; Ratih, Yanisworo Wijaya (Fakultas Pertanian, Universitas Janabadra, 2023)
Bigaran Village, which is located in the Menoreh Hills, has a hilly topography and is dominated by dry land which is thought to be lacking in nutrients. Evaluation of soil fertility is required to diagnose nutrient problems in the soil. This research was conducted with the aim of identifying soil chemical properties, determining soil chemical fertility status, and making a map of soil chemical fertility status in Bigaran Village Research management includes field surveys, determination of sample point locations, soil sampling, laboratory analysis of soil chemical properties, and evaluation of soil chemical fertility. The research was conducted from February to March 2023. Assessment of soil fertility status based on the 1995 soil fertility technical guidelines. Representative sample points were determined purposively based on the results of overlaying thematic maps (Slope Slope Map, Land Use Map, and Soil Type Map) and obtained 13 land units. The research of results showed that the Cation Exchange Capacity (CEC) values at the study sites ranged from 12.61-27.76 me/100g, Base Saturation values (KB) from 34.96-67.88%, P2O5 HCl content 25% 20.24 -105.53 mg/100g, K2O content between 15.26-128.12 mg/100g, C-Organic content ranging from 0.48-1.35%, N-Total content 0.10-0.17%, pH content 5.78-6.49%. Of the 13 sample points tested, all showed low soil fertility status. Map of Soil Chemical Fertility Status in Bigaran Village presented at a scale of 1:12,000. Low soil fertility status is symbolized in yellow. Keywords : Fertility Status, Menoreh Hills, Bigaran Village, Map INTISARIDesa Bigaran yang berada di Perbukitan Menoreh memiliki topografi berbukit serta didominasi oleh lahan kering yang diduga minim akan unsur hara. Diperlukan evaluasi kesuburan tanah untuk mendiagnosa masalah-masalah keharaan dalam tanah. Penelitian ini dilakukan dengan tujuan untuk mengidentifikasi sifat kimia tanah, menentukan status kesuburan kimia tanah, dan membuat peta status kesuburan kimia tanah Desa Bigaran. Tata laksana penelitian meliputi survey lapangan, penentuan lokasi titik sampel, pengambilan sampel tanah, analisis laboratorium sifat kimia tanah, dan evaluasi kesuburan kimia tanah. Penelitian dilakukan pada bulan Februari sampai Maret 2023. Penilaian status kesuburan tanah berdasarkan petunjuk teknis kesuburan tanah 1995. Titik sampel pewakil ditentukan secara purposive berdasarkan hasil overlay peta tematik (Peta Kemiringan Lereng, Peta Penggunaan Lahan, dan Peta Jenis Tanah) dan didapatkan 13 satuan lahan. Hasil penelitian menunjukkan nilai Kapasitas Tukar Kation (KTK) pada lokasi penelitian berkisar antara 12,61-27,76 me/100g, nilai Kejenuhan Basa (KB) dari 34,96-67,88%, kandungan P2O5 HCl 25% 20,24-105,53 mg/100g, kandungan K2O antara 15,26-128,12 mg/100g, kandungan C-Organik berkisar antara 0,48-1,35%, kandungan N-Total 0,10-0,17%, kandungan pH 5,78-6,49% Dari 13 titik sampel yang diuji, semua menunjukan status harkat kesuburan tanah rendah. Peta Status Kesuburan Kimia Tanah Desa Bigaran disajikan dengan skala 1:12.000. Status kesuburan tanah rendah disimbolkan dengan warna kuning. Kata kunci : Status Kesuburan, Perbukitan Menoreh, Desa Bigaran, Peta